Significance of trans-cerebellar diameter over other biometric parameters in the estimation of gestational age - Imran Nazir Salroo; Mohd Farooq Mir; Zahoor Ahmad Raina; Shazia Bashir; Musaddiq Rafiq Bhat (Asian Journal of Medical Sciences, 2024)
Background: Trans-cerebellar diameter (TCD) is a crucial fetal biometric parameter used in modern radiology to assess the progress of fetal growth which is vital for prosperous maternal and fetal well-being. Despite advances in ultrasound technology, the accurate measurement of fetal biometers continues to pose considerable challenges. TCD provides a more accurate gestational age, especially in late pregnancy when other parameters may be less reliable due to organic conditions. Aims and Objectives: The aim of this study was to evaluate the significance of TCD as a reliable biometric parameter in estimating gestational age and to measure the TCD in different gestational ages and establish a reference range. Assessing the correlation between TCD and other biometric parameters to that of gestational age. Materials and Methods: A cross-sectional study was conducted at SKIMS MCH Bemina, with 60 pregnant female participants recruited in the study, with consecutive purposive sampling used in the study. Consent was obtained with ethical clearance sought. The correlation between TCD, biparietal diameter (BPD), and crown-rump length (CRL) with gestational age was evaluated using the Statistical Package for the Social Sciences 24.0 to determine the strength of these relationships. Results: The study found strong correlations between fetal biometric measurements and gestational age: TCD (r=0.995), BPD (r=0.993), and CRL (r=0.988). A linear increase in BPD and CRL with increasing gestational age was observed, consistent with previous research the TCD was found particularly as a strong reliable parameter with a higher correlation for assessing fetal growth, especially in cases where other measurements may be less reliable. Conclusion: Findings suggest that TCD could be a valuable addition to standard fetal biometric measurements in clinical practice. The strong correlation between TCD and gestational age has pivotal implications for improving gestational age estimation. More research is needed to emphasize the use of TCD across many population samples and to explore its potential in fetal growth assessment.